NILAI DIAGNOSTIK UJI TROPONIN I KUANTITATIF METODE IMMUNOKROMATOGRAFI - Siti Fatonah; Anik Widijanti; Tinny Endang Hernowati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2007)
Cardiac troponins are the most sensitive and specific biochemical markers of myocardial damage but there is no standardization of WHO for cardiac troponin I, resulting in a variability for diagnostic value. It is necessary to determine diagnostic value for a new kitof troponin I. To evaluate a new quantitative immunochromatography assay for troponin I at a various cut off level. A cross sectionalstudy was conducted in 64 patients with acute myocardial infarction (AMI) and 55 non-AMI as control from February to September2007. The level of cardiac troponin I (cTnI) was measured and determined it diagnostic value at a various cut off level. The sensitivity,specificity, PPV and NPV of this assay were 91%, 91%, 92% and 89% at cut off level of 1,0 ng/ml (according to the kit), respectively.The cut off of cTnI were divided into five levels: 0.8, 1.0, 1.2, 1.5, and 2.0 with the area under curve were 0.923, 0.908, 0.912, and0.897, respectively. The sensitivity were 94%, 91%, 86%, 81% and 72%, respectively, the specificity were 91%, 91%, 96%, 98% and98%, respectively. This rapid diagnostic test is sensitive and specific to diagnose an acute coronary syndromes.